Reduction in cardiolipin decreases mitochondrial spare respiratory capacity and increases glucose transport into and across human brain cerebral microvascular endothelial cells. Issue 1 (4th September 2016) - Nguyen, Hieu M.; Mejia, Edgard M.; Chang, Wenguang; Wang, Ying; Watson, Emily; On, Ngoc; Miller, Donald W.; Hatch, Grant M.
Abstract : Abstract: Microvessel endothelial cells form part of the blood–brain barrier, a restrictively permeable interface that allows transport of only specific compounds into the brain. Cardiolipin is a mitochondrial phospholipid required for function of the electron transport chain and ATP generation. We examined the role of cardiolipin in maintaining mitochondrial function necessary to support barrier properties of brain microvessel endothelial cells. Knockdown of the terminal enzyme of cardiolipin synthesis, cardiolipin synthase, in hCMEC/D3 cells resulted in decreased cellular cardiolipin levels compared to controls. The reduction in cardiolipin resulted in decreased mitochondrial spare respiratory capacity, increased pyruvate kinase activity, and increased 2‐deoxy‐[ 3 H]glucose uptake and glucose transporter‐1 expression and localization to membranes in hCMEC/D3 cells compared to controls. The mechanism for the increase in glucose uptake was an increase in adenosine‐5′‐monophosphate kinase and protein kinase B activity and decreased glycogen synthase kinase 3 beta activity. Knockdown of cardiolipin synthase did not affect permeability of fluorescent dextran across confluent hCMEC/D3 monolayers grown on Transwell ® inserts. In contrast, knockdown of cardiolipin synthase resulted in an increase in 2‐deoxy‐[ 3 H]glucose transport across these monolayers compared to controls. The data indicate that in hCMEC/D3 cells, spare respiratory capacity is dependent on cardiolipin. In addition, reduction in cardiolipin in these cells alters their cellular energy status and this results in increased glucose transport into and across hCMEC/D3 monolayers. Microvessel endothelial cells form part of the blood–brain barrier, a restrictively permeable interface that allows transport of only specific compounds into the brain. In human adult brain endothelial cell hCMEC/D3 monolayers cultured on Transwell ® plates, knockdown of cardiolipin synthase results in decrease in mitochondrial cardiolipin and decreased mitochondrial spare respiratory capacity. The reduced cardiolipin results in an increased activity of adenosine monophosphate kinase (pAMPK) and protein kinase B (pAKT) and decreased activity of glycogen synthase kinase 3 beta (pGSK3β) which results in elevated glucose transporter‐1 (GLUT‐1) expression and association with membranes. This in turn increases 2‐dexoyglucose uptake from the apical medium into the cells with a resultant 2‐deoxyglucose movement into the basolateral medium. Abstract : Microvessel endothelial cells form part of the blood–brain barrier, a restrictively permeable interface that allows transport of only specific compounds into the brain. In human adult brain endothelial cell hCMEC/D3 monolayers cultured on Transwell ® plates, knockdown of cardiolipin synthase results in decrease in mitochondrial cardiolipin and decreased mitochondrial spare respiratory capacity. The reduced cardiolipin results in an increased activity of adenosine monophosphate kinase (pAMPK) and protein kinase B (pAKT) and decreased activity of glycogen synthase kinase 3 beta (pGSK3β) which results in elevated glucose transporter‐1 (GLUT‐1) expression and association with membranes. This in turn increases 2‐dexoyglucose uptake from the apical medium into the cells with a resultant 2‐deoxyglucose movement into the basolateral medium.